2016
DOI: 10.1097/brs.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Lordosis Minus Thoracic Kyphosis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…As pelvic parameters play a role in compensatory mechanisms [ 25 ], finding out the possible factors for T1 sagittal angle might be as equally important as finding out the predictors for the whole sagittal balance. In addition, our previous study [ 12 , 13 ] also found that LL and TK were important contributors to sagittal balance. Therefore, we speculated that LL and TK might play a role in maintaining T1 sagittal angle and could be changed in the surgical procedure through osteotomy to restore the whole sagittal balance.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As pelvic parameters play a role in compensatory mechanisms [ 25 ], finding out the possible factors for T1 sagittal angle might be as equally important as finding out the predictors for the whole sagittal balance. In addition, our previous study [ 12 , 13 ] also found that LL and TK were important contributors to sagittal balance. Therefore, we speculated that LL and TK might play a role in maintaining T1 sagittal angle and could be changed in the surgical procedure through osteotomy to restore the whole sagittal balance.…”
Section: Discussionmentioning
confidence: 85%
“…But whether T1 sagittal angle could represent sagittal balance more accurately than other sagittal parameters including SVA, TPA (T1 pelvic angle) and T1SPI (T1 spinopelvic inclination) remains unclear. In addition, our team has found great impacts of lumbar lordosis (LL) and thoracic kyphosis (TK) on maintenance and prediction of sagittal balance, which are considered novel regional predictors for sagittal balance [ 12 , 13 ]. Therefore, we speculated that LL and TK may be important contributors to T1 sagittal angle and sagittal balance, and we could restore sagittal balance through T1 sagittal angle by changing TK and LL in the surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, Schwab et al 17 brought out standardized evaluation of the sagittal plane and the goal for correction surgery in adult spinal deformity: SVA <50 mm, PI-LL <10° and PT < 25°, which had been widely used in clinical practice. Moreover, another study 18 demonstrated that LL-TK could be a good predictor for sagittal balance in Chinese elderly people, which reflected the regional compensatory mechanism and significantly associated with SVA. Our research confirmed that the pelvic parameters, the matching between spine and pelvic parameters, and the adaptation of thoracic and lumbar curvatures also played an important role for maintaining sagittal balance in patients with degenerative lumbar kyphoscoliosis.…”
Section: Discussionmentioning
confidence: 94%
“…To rebalance the forward moving center of gravity, the compensatory mechanism involved in the spine (decrease in TK and extension of adjacent segments), pelvis (pelvic retroversion, in other words, increase in PT), and lower extremities (flexion of knee and extension of ankle). As proposed by previous study, LL-TK accounted for the local compensatory mechanism, and LL-TK > 0° could predict a good sagittal balance in elderly population since TK could decrease to compensate the loss in LL [11]. In the long-fixed spine of patients after corrective surgery, the fused sagittal alignment, including lumbar and thoracic curve, as well as pelvic rotation, limited the regional compensatory mechanism: decreased thoracic kyphosis and increased pelvic tilt.…”
Section: Discussionmentioning
confidence: 98%
“…Apart from these classical sagittal modifiers, another study demonstrated that lumbar lordosis minus thoracic kyphosis (LL-TK) could be a good predictor for sagittal balance in Chinese elderly people [11], since LL-TK reflected the regional compensatory mechanism and significantly associated with SVA. Realizing the importance of this regional predictor, we speculated that LL-TK could also be a good parameter to guide the correction surgery for patients with ADS, which has not been addressed by the previous studies.…”
Section: Introductionmentioning
confidence: 99%